Policy-making in the treasury : explaining britain's chosen path on european economic and monetary union - Smith, Matthew; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Going behind the doors of the Treasury and Number 10, this book explores why successive British Prime Ministers from Callaghan to Blair have been hesitant towards European Economic and Monetary Union. It uses official documents and interviews with former ministers to understand discussions that took place at the heart of government.
Keywords: Science; Science; Science, general